ESTETIKA (DALAM) DESAIN - FX Widyatmoko (Institut Seni Indonesia Yogyakarta, 2012)
Aesthetics is a word that is often present in the areas of art, including fine art. However, in thearea of visual communication design aesthetic rarely spoken words compared with the area of fine arts(fine arts). Not that there are no problems in the design aesthetic. Aesthetic issue still exists, but it is rarelyused as a design concept design. Even the design of the study area, there are aesthetic studies. However,the study could have imagined aesthetic has a great distance to the aesthetics of everyday design. There isalso an effort to facilitate the understanding of aesthetics is to provide the name of a visual strategy(Andry Masri, Jalasutra, 2010). However, the strategy also has not explained the visual aesthetic studiesare very diverse. The phrase is intended to facilitate common aesthetic learned, particularly for the needsof design planning (especially product design).This paper aims to offer a way to understand the aesthetic rather than through understanding, butto find the position of each design aesthetic in visual communication design. The objects that wereexamined in the two final ISI Visual Communication Design (one object assessment, the object creation),as well as a book cover design. The goal is clear, to give an overview of the aesthetic. Hopefully, thegrowing diversity of aesthetic closer to the day-to-day. In short, bringing together academic research,design work, the aesthetic experience everyday.